Maritime Law Management Integration: SOLAS-STCW-MARPOL Educational Effectiveness in Port Operations - Tata Heru Prabawa (JUMINTAL: Jurnal Manajemen Informatika dan Bisnis Digital, 2025)
Background: Contemporary maritime management requires integration of SOLAS, STCW, MARPOL, and Port State Control regulations with operational decisions. Educational effectiveness in developing maritime law management competencies remains under-examined. Objectives: Investigated how effectively IMO-based maritime legal education develops management competencies for coordinating SOLAS compliance, STCW leadership, MARPOL stewardship, and PSC readiness. Methodology: Qualitative study with ten maritime professionals examining maritime law management effectiveness across regulatory domains. Results: Strong theoretical foundation (7.6/10) but significant management application gaps in SOLAS decision-making (1.6-point expert-graduate gap), STCW team management (1.4-point gap), and PSC preparedness (1.5-point gap). Conclusions: Enhanced maritime law management integration training could significantly improve regulatory management competency development.